Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1074/jbc.m608817200
|View full text |Cite
|
Sign up to set email alerts
|

CD30 Activates Both the Canonical and Alternative NF-κB Pathways in Anaplastic Large Cell Lymphoma Cells

Abstract: waf1 . Furthermore, p21 waf1 expression and cell cycle arrest were found to depend predominantly on the canonical NF-B pathway, since it was reversed by RNA interference-mediated suppression of RelA. In contrast, suppression of the p100/p52 NF-B subunit had little effect on p21 waf1 . These data reveal that in ALCL cells, in contrast to other cell types, CD30 stimulation elicits p21 waf1 -mediated arrest through the canonical but not the alternative NF-B pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
78
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 42 publications
13
78
0
5
Order By: Relevance
“…CD30 expression was also correlated with RELB and p52/RELB expression (Figure 2a). Activation of the alternative NF-κB pathway by CD30 has been shown in Hodgkin lymphoma 36 and anaplastic large-cell lymphoma, 37 and our results could suggest crosstalk between the alternative NF-κB pathway and CD30 signaling in DLBCL. DLBCL with p52 expression negatively correlated with BCL2 expression and BCL2 rearrangement (Figures 2b and c).…”
Section: Discussionsupporting
confidence: 71%
“…CD30 expression was also correlated with RELB and p52/RELB expression (Figure 2a). Activation of the alternative NF-κB pathway by CD30 has been shown in Hodgkin lymphoma 36 and anaplastic large-cell lymphoma, 37 and our results could suggest crosstalk between the alternative NF-κB pathway and CD30 signaling in DLBCL. DLBCL with p52 expression negatively correlated with BCL2 expression and BCL2 rearrangement (Figures 2b and c).…”
Section: Discussionsupporting
confidence: 71%
“…It has been shown that stimulation of CD30 signaling activates alternative NF-kB signaling in HRS cells. 18,19 As expected, NF-kB p52 levels remained stable upon GSI XII treatment in CD30-stimulated L540cy cells (Figure 5b, left panel). As a result, loss of cell viability and apoptosis induction were alleviated in L540cy cells, as evidenced by CellTiter-Glo assay and analysis of poly-(ADP-ribose) polymerase cleavage (Figure 5b, left and right panels).…”
Section: Stimulation Of Alternative Nf-kb Signaling Rescues Hrs Cellssupporting
confidence: 77%
“…[15][16][17] Moreover, it has been demonstrated that stimulation of CD30 signaling either by agonistic receptor antibodies or by CD30 ligand induces alternative NF-kB signaling in HRS cells. 18,19 However, one study showed that CD30 signaling is absent in HRS cells. 20 Therefore, it remains largely unknown how the alternative NF-kB pathway is activated and whether it has a functional role in HRS cell growth and survival.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of CD30 by CD30L has previously been shown to cause ERK phosphorylation and NF-kB activation in HRS cell lines (29)(30)(31), and, indeed, we observed increased ERK1/2 phosphorylation and increases in the activity of the alternative NF-kB pathway upon lestaurtinib treatment in all analyzed HRS cell lines. TRAIL usually induces apoptosis in tumor cells via the TRAIL-Rassociated DISC.…”
Section: Discussionsupporting
confidence: 79%
“…CD30, a cell surface TNF receptor (TNFR) expressed by most HRS cells and HRS cell lines (28), has been shown to activate the MEK/ERK pathway and the classical and alternative NF-kB pathways upon binding of its ligand (29)(30)(31). The observed increases in ERK1/2 phosphorylation upon lestaurtinib treatment are thus most likely due to the CD30L upregulation.…”
Section: Lestaurtinib Activates the Alternative Nf-kb Pathway In Hrs mentioning
confidence: 99%